Load shedding strategies for preventing cascading failures in power grid - Pahwa, Sakshi; Scoglio, Caterina M.; Das, Sanjoy; Schulz, Noel N. (My University, 2013)
Load shedding has always been a commonly adopted method in emergency situations to maintain power system reliability. Several load reduction strategies have been suggested in the past but most are complex and not scalable. In this paper, we have proposed and thoroughly investigated three load shedding strategies to prevent cascading failures in power grid. The first strategy is a base line case called the homogeneous load shedding strategy. It reduces load homogeneously in all the buses of the system. This strategy is extremely simple and fast, and these properties motivate its use in some specific scenarios in spite of its inefficiencies. Next, to accurately find the location and amount of load shedding, we propose a linear optimization formulation which is much more efficient in overall load shedding in the system. A novel tree heuristic is proposed to overcome the drawbacks of the optimization, namely fairness and scalability. The tree heuristic is linear and very simple to implement. In general, it gives close to optimal results. The results of the tree strategy are compared with that of another existing heuristic and it is found that the tree performs equal to or better than the existing heuristic for all cases.
Keywords: Cascading failures; Mitigation strategies; Load shedding; Homogeneous Load Reduction; Optimal Load Reduction; Tree Heuristic